STRATEGI GURU KELAS DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SD NEGERI 198 CINENNUNG - Sary, Linda; Nurfadilah, Nurfadilah; Musdalifah, Musdalifah; Bakar, Abu (DIDAKTIKA, 2022)
Character is an inner trai that affeets thought, behavior, refinement and traits the humans or other living creatures possess. Character degradation or demoralization is carrenty experienced by Indonesia, this is marked by the increasing the number of criminal acts and various social deviations that infect alllcircle, both the younger and older generation. According to nashikah cited in moh.khaerul anwar that early character education in children in the first step in forming child’s character so it’s needed early education. When character education can be implemented systematically and sustainably, it’s hoped that the moral crisis that occurs in this country can be resouled and it’s expected to be able to give birte a next generation as a generation that has high moral or strong character as aspired by Indonesia netion.the type of research by researcher is qualitative research, which is a study aimed at describius and analizing phenomena events, social activities, attitudes, belief, perceptions, thoughts of people individually and group. The research approach used in this research is management approach. Management approach is a science that studies about the process of institution managing and organizational institution by involviry potential sources both human and non human to achieve desired goals. Data used in this researeh are; primary data is the type of data obtained and extracted from the source directly, the main source (school residents). Secoundary data is data that has been obtained or collected by researcher, wheather from books, journals, chart tables and others. Technique of collecting data, interview is widely used in qualitative research. And even can be said to be the main technigve of collencting data, observation is daily human activity in using five senses eyes as main tool help than other five senses susch as ears, nose, mouth and skin. Analizing data in this research refers to qualitative analisys, which is data reduction, data display and conclusid.